1976
DOI: 10.1085/jgp.67.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Side-dependent effects of internal versus external Na and K on ouabain binding to reconstituted human red blood cell ghosts.

Abstract: A B S T R A C T The side-dependent effects of internal and external Na and K on the ouabain binding rate, as promoted by inside MgATP, has been evaluated utilizing reconstituted human red blood cell ghosts. Such ghost systems provide the situation where [Nail, [K] [K]i in the absence of K0 were without effect on the ouabain binding rate. Thus, the ouabain binding rate was found to vary inversely with the rate of Na:K and K:K exchange but was independent of the rate of Na:Na exchange. The effect of K o in anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2

Year Published

1977
1977
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 45 publications
5
40
2
Order By: Relevance
“…In a recent study with red cell ghosts (Bodemann & Hoffman, 1976) Schwartz et al 1975). This particular structure of the region involved in the binding may occur once during each Na-K pump cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study with red cell ghosts (Bodemann & Hoffman, 1976) Schwartz et al 1975). This particular structure of the region involved in the binding may occur once during each Na-K pump cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In red blood cells, for example, several studies indicate that K § competes with Na § for pump sites on the inside of the cell membrane, so that an increase in [K+]i decreases the amount of Na + pumped out of the cell (Garay & Garrahan, 1973;Knight & Welt, 1974;Simons, 1974;Bodemann & Hoffman, 1976;Blostein & Chu, 1977 …”
Section: Inactivation Of ~He Electrogenic Pumpmentioning
confidence: 99%
“…Evidence indicates that external K+ counteracts glycoside binding by inducing an allosteric configurational change of the transport system. Studies on reconstituted red cell ghosts (Bodemann and Hoffman, 1976a) have provided strong support for this concept. It could be shown that the binding of ouabain is not slowed by external K + if internal K + is replaced by isotonic concentrations of biologically inactive choline chloride.…”
Section: Interaction Of Cardiac Glycosides and Na+k+ Pumpmentioning
confidence: 93%